Plasmas Containing Quasimonochromatic Electric Fields (QEFs): Review of the General Principles of Their Spectroscopy and Selected Applications - Eugene Oks (Atoms)
We review the general principles of the spectroscopy of plasmas containing quasimonochromatic electric fields (QEFs). We demonstrate that the underlying physics is very rich due to the complicated entanglement of four characteristic times: the typical time required for the formation of the quasienergy states, the lifetime of the excited state of the radiator, the typical time of the formation of the homogeneous Stark broadening by the electron microfield, and the typical time of the formation of the homogeneous Stark broadening by the dynamic part of the ion microfield. We exemplified how the shape and shift of spectral lines are affected by the mutual interactions of the three subsystems. Specifically, the interaction of the radiator with the plasma can be substantially influenced by the interaction of the radiator with the QEF, and vice versa, as well as by the interaction of the QEF and the plasma with each other. We also provide some applications of these various effects. Finally, we outline directions for future research.